Research Methodology and Scientific writing - Thomas, C.George (Ane Books Pvt. Ltd., 2020)
This revised and expanded second edition comprises 24 chapters and each chapter divided into sections of specific unts. Considering the demand of the readers, following four new chapters have been added: 1. Units and numbers 2. Guidelines for Successful Lecturing 3. Notemaking, Note-taking and Assignments 4. Plagiarism: Prevention and Cure